Optimizing reduced capture antibody conjugation to encoded hydrogel microparticles for enhanced multiplex immunoassays - Kim, Do Yeon; Kim, Jiwoo; Jang, Wookyoung; Bong, Ki Wan (Frontiers in Sensors, 2022)
Multiplex detection of protein biomarkers in biological fluids facilitates high-throughput detection using small-volume samples, thereby enhancing efficacy of diagnostic assays and proteomic studies. Graphically encoded hydrogel microparticles conjugated with capture antibodies have shown great potential in multiplex immunoassays by providing superior sensitivity and specificity, a broad dynamic range, and large encoding capacity. Recently, the process of post-synthesis conjugation of reduced capture antibodies to unreacted acrylate moieties in hydrogel particles has been developed to efficiently prevent the aggregation of capture antibodies inside particles, which occurs when using conventional conjugation methods. This direct conjugation process yielded robust assay performance through homogeneous conjugation of the capture antibodies, and avoided the use of hydrolytically unstable linker additives. However, no research has been conducted to optimize the process of conjugating capture antibodies to the particles. We here present a strategy to optimize capture antibody conjugation based on the finding that excessive addition of capture antibodies during incubation can rather lower the amount of capture antibodies conjugated to the particles for some types of capture antibodies. Based on our optimized capture antibody conjugation process, a singleplex immunoassay for a selected target was conducted. Enhanced sensitivity compared with previous studies was confirmed. We also validated the increased specificity of multiplex detection through our optimization process. We believe that the optimization process presented herein for capture antibody conjugation will advance the field of encoded hydrogel microparticle-based immunoassays.